Evaluation of Dibenzocyclooctyne and Bicyclononyne Click Reaction on Azido‐Functionalized Antifouling Polymer Brushes via Microspotting (Adv. Mater. Interfaces 16/2022). Issue 16 (3rd June 2022) - Yang, Bingquan; Wang, Yangxin; Vorobii, Mariia; Sauter, Eric; Koenig, Meike; Kumar, Ravi; Rodriguez‐Emmenegger, Cesar; Hirtz, Michael
Abstract : Antifouling Polymer Brushes In article number 2102325, Bingquan Yang, Michael Hirtz, and co‐workers investigate the efficiency of cyclooctyne click chemistry based patterned immobilization of functional compounds on azide‐bearing diblock polymer brushes. Microchannel cantilever spotting (μCS) enables spotting of microarrays on the antifouling brushes that can act as selective adhesion spots for proteins as of the favorable anti‐adhesion properties of the polymer.